NEURONAL AND SYNAPTIC ORGANIZATION OF ENTERIC NERVOUS SYSTEM - Ana Maria Fatu; Diana Ciubotariu; Magda-Ecaterina Antohe; Cristina Iordache; Codrina Ancuta; Mihai Bogdan Vâscu (Romanian Journal of Oral Rehabilitation, 2023)
The aim of present work is a double one. On the first hand we tried to collect together the newest data concerning the enteroneurons’ morphology, their association in the parietal plexuses and their synaptic interconnections. All classes of enteroneurons were discussed in detail, but, despite their diversity, we have concluded that, essentially, they can be classified as motor, sensitive and interneurons, are disposed in layers and have the same functionality as the cerebral cortex neurons. According to their neurochemistry, we have imagined reflex circuits subserving motor and secretory functions, illustrated with original diagrams. Enteroglia and interstitial cells of Cajal are also assessed in interrelation with neurilema and myolema of gut muscles fibers. The second goal of our study was focussed on serotoninergic enteroneurons, their contribution to both motor and secretory gut functions and also on synuclein production in the enteroneurons, named by us extraparietointestinal. Their contribution to trigger the initial stages of Parkinson disease is proposed.